2004
DOI: 10.1046/j.1538-7933.2003.00576.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin generation: phenotypic quantitation

Abstract: An individual's ability to generate thrombin following tissue factor stimulus was evaluated in 13 healthy male donors in a 6-month study. Thrombin generation in whole blood collected by phlebotomy, contact pathway suppressed by the presence of 100 micro g mL-1 corn trypsin inhibitor, was initiated by the addition of 5 pm tissue factor/10 nm phospholipid. Reactions were quenched at 20 min by the addition of an ethylenediaminetetraacetic acid (EDTA), benzamidine, FPRck cocktail. Thrombin generation was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
100
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 50 publications
(95 reference statements)
7
100
0
Order By: Relevance
“…The extremes were £ 311nM (P5) and ‡ 650nM (P95). This range of thrombin maximum levels in the LETS control population (n ¼ 473), overlap the maximum levels determined in an empirical whole blood study of 13 healthy individuals (245-775nM, with a cumulative mean of 414nM, SD 111nM) (26). The mean of the population for total thrombin (Fig 2D) was 92lMs (SD 19lMs) with a range of 39-177lMs.…”
Section: Thrombin Parameterssupporting
confidence: 60%
See 1 more Smart Citation
“…The extremes were £ 311nM (P5) and ‡ 650nM (P95). This range of thrombin maximum levels in the LETS control population (n ¼ 473), overlap the maximum levels determined in an empirical whole blood study of 13 healthy individuals (245-775nM, with a cumulative mean of 414nM, SD 111nM) (26). The mean of the population for total thrombin (Fig 2D) was 92lMs (SD 19lMs) with a range of 39-177lMs.…”
Section: Thrombin Parameterssupporting
confidence: 60%
“…The second approach focuses on developing tests for assessing hemostatic competence, with a primary focus on the measurement of thrombin generation. These in vitro approaches include the whole blood thrombin generation test [23,24], the endogenous thrombin potential in plasma [25], or derived methods in which markers of procoagulant [26,27] or fibrinolytic activity [28][29][30] are measured.…”
Section: Introductionmentioning
confidence: 99%
“…Both inherited (genetic) and acquired (environmental and therapeutically induced) haemostatic variations can lead to significant alterations in these profiles [23,24]. It has been shown that the coagulation factors show remarkable interindividual variation, even among healthy subjects [24].…”
Section: What Is "Normal" Thrombin Generation?mentioning
confidence: 99%
“…It has been shown that the coagulation factors show remarkable interindividual variation, even among healthy subjects [24]. Several technologies have been developed to directly or indirectly measure thrombin generation profiles [23,24,25].…”
Section: What Is "Normal" Thrombin Generation?mentioning
confidence: 99%
“…Thrombin generation assays can be used to define an individual's phenotype through the use of the phases of thrombin generation (initiation, propagation, termination) which are governed by the underlying kinetic reactions and can provide descriptors of the coagulation process (eg, rates, levels, and timing of thrombin formation and inhibition) 24. Studies in the healthy population have shown that thrombin generation dynamics differ largely between individuals, but are relatively stable over time in a given individual, supporting the concept that they may have utility as a phenotypic marker 25, 26, 27. The mechanism‐based bridge between thrombin generation assays and individualized risk prediction is plasma composition–based computational modeling 28, 29.…”
Section: Introductionmentioning
confidence: 99%